Hustle Culture Mahasiswa Universitas Indo Global Mandiri Palembang: Analisis Stoikisme Marcus Aurelius: Analisis Stoikisme Marcus Aurelius - Dike, Dike Mandala Putra; Syefriyeni; Jamhari (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2024)
This research is motivated by the problem of workaholic lifestyle (Hustle Culture) for students. The purpose of this study is to find out how the form of mind and happiness for Hustle Culture students at Universitas Indo Global Mandiri Palembang using the analysis of Stoicism. The method in this study uses a qualitative descriptive research type. Data sources, namely 1. Primary Data Sources (research subjects of Students of Universitas Indo Global Mandiri Palembang), 2. Secondary Data Sources (books, literature, articles, magazines or other secondary data sources). The data collection technique includes interviews, observation and documentation as well as data analysis techniques, namely inductive-descriptive. The results this study found that Hustle Culture Students at Universitas Indo Global Mandiri mostly have inconsistencies with stoic. As the great theory of Stoicism philosophy is that the happiness obtained must be harmony with the laws of nature, thoughts that are within reach and how to represent them. Based on the analysis the fourteen cases of students with subjects seven male students and seven female students. Two male and four female students were found to be accordance with Marcus Aurelius' Stoic concept of happiness. Meanwhile, five male and three female students were not in accordance with Marcus Aurelius' Stoic. Through the data collected, six male and female students who were in accordance with Stoicism carried out Hustle Culture activities by building positive thoughts representations their work events. By not thinking about things that beyond control and line with the Universal Logos. Meanwhile, eight male and female students who were not in accordance with Stoicism represented work experienced with negative emotions and not with the Universal Logos. Key Note: 1; Hustle Culture 2; Stoicisme 3; Happiness